Recognizing and rewarding farmers' creativity through contests: Experiences and insights from four African countries - Justice A. Tambo (University of Bonn, Center for Development Research (ZEF), 2018)
This paper presents the experiences and outcomes of applying contests to elicit farmer-generated innovations and to reward outstanding farmer innovators in selected districts in Ethiopia, Kenya, Malawi and Zambia. The contests attracted 349 eligible entries, most of which were submitted by male innovators. The identified innovations were mainly technically oriented practices, and only very few institutional innovations were recognized. The most common domains of innovations were related to livestock (40%), crop management (26%), storage (10%), soil and water management (8%) and farm tools and implements (5%). In particular, many of the innovators were using local resources to develop plant-based biopesticides and ethnoveterinary medicines in order to reduce production costs and improve food production. The findings of this study suggest that farmers are active experimenters who continuously generate remarkable and locally adapted innovations, which can indirectly contribute to efforts to achieve sustainable agricultural intensification or to make agriculture climate smart. The study concludes that farmers possess valuable ethnobotanical knowledge and innovation-generating potential that need to be harnessed and supported; and contest is an effective means to scout and acknowledge farmer innovators while simultaneously raising awareness of farmer innovation approach among relevant stakeholders.
Keywords: 330; Contest; prize rewards; farmer-generated innovations; biopesticides; ethnoveterinary practices